Institutions and agency in CSR strategy: an empirical investigation of development and implementation - Bondy, Krista (2008)
This PhD research started from an interest in how corporate social responsibility (CSR) works in practice and in identifying how to motivate companies to actively and meaningfully engage in CSR. It was further motivated by findings from previous research projects (Bondy et al 2004, Bondy 2006, Bondy 2007, Bondy et al 2008 forthcoming) which highlighted both the need for research in the area of CSR implementation, and the interesting issues around how corporations deal with the complexities of governing themselves in a global marketplace.